PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PRIME SUPPLY SOLUTIONS KOTA DEPOK - Gilang Surya Adi; Liawati (Journal of Research and Publication Innovation, 2025)
This study aims to determine the positive and significant effects of leadership style and work environment on employee performance at PT Prime Supply Solutions in Depok, both partially and simultaneously. The research focuses on understanding the influence of leadership style and work environment on employee performance within the company. A total of 63 samples were used, employing a saturated sampling technique from the entire population of employees at PT Prime Supply Solutions in Depok. This research utilized a quantitative method with a Likert scale. The analysis included descriptive analysis, data instrument testing, classical assumption testing, quantitative analysis, and hypothesis testing. Based on multiple regression calculations, the variables of leadership style (X1) and work environment (X2) produced the equation Y = 0.672 + 0.537 X1 + 0.416 X2. The t-test for Leadership Style yielded a t-value greater than the t-table (5.035 > 2.000) with a significance value of 0.00 < 0.05, leading to the rejection of Ho and acceptance of H1, indicating that leadership style affects employee performance. The t-test for Work Environment also showed a t-value greater than the t-table (4.092 > 2.000) with a significance value of 0.00 < 0.05, resulting in the rejection of Ho and acceptance of H2, meaning that work discipline influences employee performance. The F-test produced an F-value greater than the F-table (189.915 > 3.15) with a significance value of 0.00 < 0.05, leading to the rejection of Ho and acceptance of H3, indicating that leadership style and work environment simultaneously affect employee performance. The company needs to conduct in-depth surveys to understand issues related to access to technology and resources, as well as a thorough evaluation of leadership style with a focus on enhancing employee engagement. This will ensure that the human resources within the company are more comfortable and improve communication with superiors in the future.